The happy farmer: Self-employment and subjective well-being in rural Vietnam - Thomas Markussen; Maria Fibæk; Finn Tarp; Nguyen Do Anh Tuan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Using survey data from rural Vietnam, this paper documents a statistically significant, positive effect of self-employment in farming on subjective well-being. Wage workers are less happy than farmers across a range of different types of wage jobs. These results suggest that structural transformation is associated with a psychological cost, which may contribute to explaining earnings gaps between sectors and types of employment. We also investigate other determinants of happiness, such as income, age, gender, children, ethnicity, marital status, schooling, landlessness, migration, social networks and shocks. Our results from rural areas in a dynamic developing country context are remarkably similar to findings about subjective well-being from developed countries, with entirely different cultures and levels of economic development.
Keywords: I31; J24; J43; O17; 330; happiness; self-employment; wage work; agriculture; Vietnam